Selective detection of dopamine in the presence of ascorbic acid using carbon nanotube modified screen-printed electrodes - Moreno, Mónica (2010)
This work reports on the performance of carbon nanotube modified screen-printed electrodes (SPE-MWCNT) for the selective determination of dopamine (DA) in the presence of ascorbic acid (AA) by adsorptive stripping voltammetry (AdSV). Several operating conditions and parameters were examined including the electrochemical pre-treatment and the previous AA interaction and DA accumulation in the presence AA at physiological conditions. Under the chosen conditions, DA peak current of differential pulse voltammograms increases linearly with DA concentration in the range of 5.0 × 10-8 to 1.0 × 10-6 mol L-1 with a limit of detection of 1.5 × 10-8 mol L-1 in connection with 600 s accumulation time. The sensitivity obtained for DA was independent from the presence or absence of AA; therefore, the proposed method can be readily applied to detect DA in real samples. The proposed methodology was successfully used for the quantification of DA in urine samples.